Nature of Comparative Linguistics - Odina Abdugopporova Hoshimjon kizi (Scholars Digest Publishing, 2023)
Language is a social phenomenon that is created in the society of individuals and serves as a means of communication. Its social nature is manifested in serving society, not individual. Language is the main tool that expresses all the cultural and scientific wealth created by mankind in the course of historical development and is inherited from generation to generation.
Keywords: Language, emergence of language, linguistics, society, object.